Productivity: A Hidden Engine of Growth in Philippine Remittance Inflows under Gravity Model (Pre-Pandemic Period) - Navarro, Maria Jessica; Peñafiel, Nicole Anne; Magpantay, Ederliza (IJOSMAS, 2023)
As the primary source of income for the Philippines, remittances have increased in the past few years. This study employed the gravity model to determine the extent of the definition of the gravitational and controlled variables of remittances. This study is the first in the literature to examine remittances in the Philippines using the gravity model. Using data from 15 key host nations from 1996 to 2017, panel least squares data with a fixed effect model was adopted using the Housman test to tackle the time-invariant problem. The analysis found that the GDP of the sending country, population, and labor productivity are statistically significant and positively affect the remittance inflow in the Philippines. Whereas distance, the GDP of the recipient country, migrant stock, and political stability are statistically insignificant factors in the remittance inflow into the Philippines.